External validation of and improvement upon a model for the prediction of placenta accreta spectrum severity using prospectively collected multicenter ultrasound data - Kolak, Magdalena; Gerry, Stephen; Huras, Hubert; Al Naimi, Ammar; Fox, Karin A; Braun, Thorsten; Stefanovic, Vedran; van Beekhuizen, Heleen; Morel, Olivier; Paping, Alexander; Bertholdt, Charline; Calda, Pavel; et al. (Acta obstetricia et gynecologica Scandinavica, 2025)
INTRODUCTION: This study aimed to validate the Sargent risk stratification algorithm for the prediction of placenta accreta spectrum (PAS) severity using data collected from multiple centers and using the multicenter data to improve the model. MATERIAL AND METHODS: We conducted a multicenter analysis using data collected for the IS-PAS database. The Sargent model's effectiveness in distinguishing between abnormally adherent placenta (FIGO grade 1) and abnormally invasive placenta (FIGO grades 2 and 3) was evaluated. A new model was developed using multicenter data from the IS-PAS database. RESULTS: The database included 315 cases of suspected PAS, of which 226 had fully documented standardized ultrasound signs. The final diagnosis was normal placentation in 5, abnormally adherent placenta/FIGO grade 1 in 43, and abnormally invasive placenta/FIGO grades 2 and 3 in 178. The external validation of the Sargent model revealed moderate predictive accuracy in a multicenter setting (C-index 0.68), compared to its higher accuracy in a single-center context (C-index 0.90). The newly developed model achieved a C-index of 0.74. CONCLUSIONS: The study underscores the difficulty in developing universally applicable PAS prediction models. While models like that of Sargent et al. show promise, their reproducibility varies across settings, likely due to the interpretation of the ultrasound signs. The findings support the need for updating the current ultrasound descriptors and for the development of any new predictive models to use data collected by different operators in multiple clinical settings.
Keywords: hodnocení rizik; Risk Assessment; Placenta Accreta; probability; placenta accreta spectrum; Pregnancy; těhotenství; Adult; Prospective Studies; dospělí; Ultrasonography, Prenatal; algoritmy; reprodukovatelnost výsledků; ultrasonografie prenatální; abnormal invasive placenta; Severity of Illness Index; Reproducibility of Results; prediction model; lidé; ženské pohlaví; placenta accreta; Humans; Algorithms; prediktivní hodnota testů; stupeň závažnosti nemoci; abnormal adherent placenta; Female; Predictive Value of Tests; prospektivní studie